Neologisms in the Bosnian Language Motivated by Proper Names - Amela Šehović (Društvene i Humanističke Studije)
The subject of this research paper is neologisms motivated by proper names. The research aims to determine their presence in the Bosnian language, the context of their usage and their formation methods, as well as the sociolinguistic factors that affect their occurrence and potential disappearance. The analysis was conducted on a corpus extracted from printed media and their electronic editions, as well as from Bosnian-Herzegovinian portals. It has therefore been concluded that many of these neologisms are lexemes motivated by surnames, and somewhat fewer by personal names, names of countries, cities, regions and organizations. In this context, the most frequent word formation basis consists of personal names and surnames of politicians, both global and regional, as well as abbreviated names of political parties. In addition to suffixes, some suffixoids also take part in the formation of these lexemes, and most of the derivatives have a negative overtone, referring to individuals and processes. These derivatives often appear in headlines, subheadings, and captions of newspaper articles, while their instability in general usage is indicated by placing them in quotation marks. The paper also points to their uncertain fate regarding their survival in the lexical corpus of the Bosnian language, as this depends on external, extralinguistic factors.